Impact of competition and concentration on bank income smoothing in Central and Eastern European countries - Shala, Albulena (2024)
Purpose: This study examines the impact of competition and concentration on bank income smoothing in Central and Eastern European (CEE) countries. Design/methodology/approach: The two-step system GMM method was used to analyse the impact of competition and concentration on bank income smoothing in 17 CEEs from 2004 to 2015. Findings: Loan loss provisions (LLPs) are negatively related to bank competition and concentration. The authors find no evidence for income smoothing using LLPs in a high-competition or high-concentration environment. Research limitations/implications: A limitation of the study is that the analysis was restricted to commercial banks. The authors did not examine investment banks or microfinance banks in this study. Also, not having access to databases does not allow them to include recent years in the study. Practical implications: CEE commercial banks will likely keep fewer provisions or engage in under-provisioning when they face intense competition, and this can expose them to credit risk, which may threaten their stability. Originality/value: This study is the first to investigate the effect of concentration and competition on income smoothing among CEE banks.